Concise synthesis of the macrocyclic core of Rhizopodin by a heck macrocyclization strategy - Dieckmann, Michael; Rudolph, Sven; Dreisigacker, Sandra; Menche, Dirk (The journal of organic chemistry, 2012)
A highly convergent synthesis of the central dimeric core of the potent antibiotic macrolide rhizopodin is reported. Notable features of the highly concise route include an eﬀective preparation of the key C8-C22 building block based on an iridium-catalyzed Krische allylation and a chemoselective crosscoupling approach toward the macrocycle involving a highly advantageous Heck reaction for macrocyclization.